2016
DOI: 10.12669/pjms.323.9779
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk score in Rheumatoid Arthritis

Abstract: Objective:To determine the 10-year Cardiovascular risk score with QRISK-2 and Framingham risk calculators in Rheumatoid Arthritis and Non Rheumatoid Arthritis subjects and asses the usefulness of QRISK-2 and Framingham calculators in both groups.Methods:During the study 106 RA and 106 Non RA patients age and sex matched participants were enrolled from outpatient department. Demographic data and questions regarding other study parameters were noted. After 14 hours of fasting 5 ml of venous blood was drawn for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…In the present study, the mean age of the patients with RA was 45.3 ± 11.5 years. Our results align with that of Wagan et al (2016), who reported a similar mean age of 45.1±9.5 years among patients with RA at Sheikh Zayed Federal Post Graduate Medical Institute, Lahore, Pakistan [16]. Imran et al…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the mean age of the patients with RA was 45.3 ± 11.5 years. Our results align with that of Wagan et al (2016), who reported a similar mean age of 45.1±9.5 years among patients with RA at Sheikh Zayed Federal Post Graduate Medical Institute, Lahore, Pakistan [16]. Imran et al…”
Section: Discussionsupporting
confidence: 91%
“…The QRISK-2 scores were also positively correlated with plasma L5% or L5 levels, whereas Framingham score were not. This discrepancy may be explained by the more inclusive calculation design of QRISK-2 scoring, additionally enrolling RA disease, ethnicity, chronic kidney disease, and atrial fibrillation as factors in the risk assessment [28,40]. During the follow-up period of more 2 years, CVD developed in three RA patients, all who had carotid atherosclerosis and markedly higher L5% (22.1%, 9.8%, and 7.5%) and L5 levels (21.9 mg/dL, 10.8 mg/dL, and 12.5 mg/dL) than did patients who did not have a CVD event.…”
Section: Discussionmentioning
confidence: 99%
“…RA leads not only to the destruction of cartilage and bone but also to system damage including cardiovascular, pulmonary, and endocrine system [ 27 , 28 ]. This demonstrated a relationship between inflammatory factors and insulin resistance [ 29 31 ].…”
Section: Inflammation and Abnormal Glucose Metabolismmentioning
confidence: 99%